Advanced concepts and methods for very high intensity accelerators. (16th October 2014) - Nghiem, P.A.P.; Chauvin, N.; Comunian, M.; Oliver, C.; Simeoni, W.; Uriot, D.; Valette, M.
Abstract: For very high intensity accelerators, not only beam power but also space charge is a concern. Both aspects should be taken into consideration for any analysis of accelerators aiming at comparing their performances and pointing out the challenging sections. As high beam power is an issue from the lowest energy, careful and exhaustive beam loss predictions have to be done. High space charge implies lattice compactness making the implementation of beam diagnostics very problematic, so a clear strategy for beam diagnostic has to be defined. Beam halo is no longer negligible. Its dynamics is different from that of the core and plays a significant role in the particle loss process. Therefore, beam optimization must take the halo into account and beam characterization must be able to describe the halo part in addition to the core one. This paper presents the advanced concepts and methods for beam analysis, beam loss prediction, beam optimization, beam diagnostic, and beam characterization especially dedicated to very high intensity accelerators. Examples of application of these concepts are given in the case of the IFMIF accelerators.